2009
DOI: 10.1038/ejhg.2009.56
|View full text |Cite
|
Sign up to set email alerts
|

Preimplantation genetic diagnosis for myotonic dystrophy type 1: upon request to child

Abstract: Preimplantation genetic diagnosis (PGD) is an alternative to prenatal diagnosis for patients at risk of transmitting an inherited disease such as myotonic dystrophy type 1(DM1) to their offspring. In this paper, the clinical application of preimplantation diagnosis for DM1 upon request to children born is described in a large cohort of risk couples. PGD could be offered to all 78 couples opting for PGD regardless of the triplet repeat size. The incidence of major complications was minimalised following a caref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 40 publications
0
10
0
1
Order By: Relevance
“…In contrast to PGD for monogenic disorders, where moral and ethical considerations are also important reasons to opt for PGD, 19 couples with rcp almost exclusively choose PGD because of fertility problems or repeated miscarriages. This bias is inherent to the problems induced by carriership of translocations.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to PGD for monogenic disorders, where moral and ethical considerations are also important reasons to opt for PGD, 19 couples with rcp almost exclusively choose PGD because of fertility problems or repeated miscarriages. This bias is inherent to the problems induced by carriership of translocations.…”
Section: Discussionmentioning
confidence: 99%
“…From 1997 onwards, with the development of a sensitive TP-PCR for detection of DM1 expansions, PGD could also be offered for half-informative (couples with both partners sharing one normal allele of the same size) or noninformative couples (couples with three normal alleles identical in size) [111]. Further improvement of the accuracy of PGD for DM1, in terms of detection of contamination of the sample and allelic drop out, was achieved by the use of multiplex PCR with combined DM1-linked markers and detection of the repeat fragments [116]. …”
Section: Genetic Testing and Counseling In Dm1mentioning
confidence: 99%
“…Report on a large cohort of DM1 patients undergoing PGD for DM1-showed that (i) it was safe in DM1-affected women after careful pretreatment assessment with regard to disease-specific complications (cardiological, anaesthetical, and obstetrical problems), (ii) delivery rate per treatment cycle was 20%, with at least one baby after two PGD cycles in almost half of the couples, and (iii) the children born were generally in good health up to 2 years of age and comparable to children born after intracytoplasmatic sperm injection for infertility and after PGD for other genetic conditions [116]. As pointed out by de Rademaeker et al [116], PGD for DM1 is a well-established procedure resulting in the birth of unaffected and mostly healthy children and should be considered as an alternative to PND in couples with concomitant infertility and couples unwilling to undergo termination of pregnancy (Table 1).…”
Section: Genetic Testing and Counseling In Dm1mentioning
confidence: 99%
See 1 more Smart Citation
“…La myotonie de Steinert peut en effet s'accompagner de troubles de la fertilité féminine, qui ont pu contribuer à l'infertilité de ce couple [2,11]. Le diagnostic maternel aurait permis un diagnostic prénatal, voire une AMP avec diagnostic préim-plantatoire [2,12]. Une autre question est posée par les consé-quences de l'AMP sur la majoration de l'expansion des codons, donc sur son rôle dans l'induction d'une forme plus sévère de la maladie chez l'enfant.…”
Section: Discussionunclassified